2023
DOI: 10.1370/afm.2943
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Shared Decision-Making Research and Practice: The Case for Black American Patients

Abstract: OBJECTIVEThe extent of shared decision making (SDM) use in the care of Black patients is limited. We explored preferences, needs, and challenges of Black patients to enhance SDM offerings. METHODSWe performed interviews with 32 Black patients receiving type 2 diabetes care in safety-net primary care practices caring predominantly for Black people. RESULTSThe following 4 themes emerged: preference for humanistic communication, need to account for the role of family in decision making, need for medical informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In the study, overwhelmingly, White clinicians had different observed levels of shared decision making with Black caregivers compared with White caregivers. The study echoes the accumulated work pointing to disparities in current shared decision making interventions and tools . It helps move the needle further to make shared decision making more accountable for different cultural norms, values, and beliefs.…”
mentioning
confidence: 56%
“…In the study, overwhelmingly, White clinicians had different observed levels of shared decision making with Black caregivers compared with White caregivers. The study echoes the accumulated work pointing to disparities in current shared decision making interventions and tools . It helps move the needle further to make shared decision making more accountable for different cultural norms, values, and beliefs.…”
mentioning
confidence: 56%
“…Without direct elicitation, clinicians must rely on their assumptions about those values and risk making a “preference misdiagnosis [ 44 ].” Those assumptions are also influenced by implicit biases related to age, race, and gender [ 45 , 46 ]. A recent analysis of facilitators for SDM among African American patients highlight patients’ desire for more medical information and the benefit of “facilitating a level-playing field interaction [ 47 ].” Relying on patients’ initial treatment preferences without exploring their values and reasoning can perpetuate disparities in care. In our study, clinicians often underestimated patients’ desire to be involved in decisions, and overestimated the extent to which patients wanted their physician to make the decision.…”
Section: Discussionmentioning
confidence: 99%
“…Those assumptions are also influenced by implicit biases related to age, race, and gender [45,46]. A recent analysis of facilitators for SDM among African American patients highlight patients' desire for more medical information and the benefit of "facilitating a level-playing field interaction [47]." Relying on patients' initial treatment preferences without exploring their values and reasoning can perpetuate disparities in care.…”
Section: Plos Onementioning
confidence: 99%
“… 10 Zisman‐Ilani and colleagues reported that patient understanding favored by storytelling in communication, to contextualize medical information, is a facilitator of SDM. 50 …”
Section: Discussionmentioning
confidence: 99%